Complexity and Idiosyncrasy at the Federal Circuit - Cahoy, Daniel R.; Oswald, Lynda J. (Science and Technology Law Review, 2018)
As a specialized intermediate appellate court with exclusive jurisdiction over all U.S. patent appeals, the Federal Circuit wields extraordinary power over the development of the language of patent law. Scholars theorize that the Federal Circuit’s isolation causes it to speak to a narrow audience (the specialized patent bar and sophisticated members of the inventive industries). In particular, the court may intentionally or subconsciously employ “jargon” to obscure difficult legal or policy issues. This Article uses recent case examples to illustrate that Federal Circuit patent doctrine does indeed suffer from two forms of obscurity related to vocabulary: complexity and idiosyncrasy. Patent system policy and goals suggest that obscurity is problematic and should be reduced. The optimal forum for concentrating on change is the Federal Circuit, but reducing obscurity while preserving the advantages of a specialized court is an enduring challenge.